Mechanism of Hyperbolic Growth Explained - NIELSEN, Ron W. (Journal of Economics Library, 2016)
Abstract. Fundamental law of growth is used to explain the mechanism of hyperbolic growth of human population and of the Gross Domestic Product (GDP). Hyperbolic growth is described by a simple mathematical formula and the explanation of its mechanism turns out to be also simple. Historical economic growth was prompted by the familiar net market force, which was on average directly proportional to the existing wealthexpressed usually as the GDP. The larger was the GDP, the stronger was the driving force and the faster was the economic growth. It is shown that this simple force generates hyperbolic growth. No other force is required. Hyperbolic growth is not assumed but derived when using this force. Historical growth of population was prompted by thebiologically driven force of procreation, which was on average approximately constant per person. This force includes the natural, familiar, biologically controlled process of births, aging and dying. Here again, hyperbolic growth is not assumed but derived when using this force.Explanation of two demographic transitions in the past 12,000 years in the growth of population and of the currently experienced transition is also proposed. Currently, economic growth and the growth of population are no longer unconstrained. Other additional forces contribute significantly to the growth process and the growth is no longer hyperbolic. Keywords. Hyperbolic growth, Mechanism of growth, Population growth, Economic growth. JEL. A10, A12, A20, B41, C02, C20, C50, Y80.